Prenatal maternal vitamin D deficiency sex‐dependently programs adipose tissue metabolism and energy homeostasis in offspring. Issue 11 (14th September 2020) - Seipelt, Eva M.; Tourniaire, Franck; Couturier, Charlène; Astier, Julien; Loriod, Béatrice; Vachon, Hortense; Pucéat, Michel; Mounien, Lourdes; Landrier, Jean‐François
Abstract: In utero environment is crucial to ensure normal development of the fetus and to program metabolic health throughout the life. Beside macronutrients, the role of micronutrients, including vitamin D, begins to be explore. The aim of this study was to decipher the impact of maternal vitamin D deficiency (VDD), in normal and high‐fat (HF) diet context, on adipose tissue metabolism and energy homeostasis in offspring, considering sex‐specific responses. Body weight, energy expenditure, and spontaneous activity was differential impacted in juvenile male and female offspring born from VDD mice. In adulthood, a HF diet combined with maternal VDD disrupted glucose homeostasis and adiposity in male offspring but not in females. Such phenotypes were associated to different transcriptomic profiles in adipose tissue, which could be related to differential modulation of plasma 17β‐estradiol concentrations. Thus, maternal VDD sex‐dependently modulated metabolic fate of the offspring, especially when associated with HF diet in adulthood.